Effects of Food Processing on In Vivo Antioxidant and Hepatoprotective Properties of Green Tea Extracts - Xiao-Yu Xu; Jie Zheng; Jin-Ming Meng; Ren-You Gan; Qian-Qian Mao; Ao Shang; Bang-Yan Li; Xin-Lin Wei; Hua-Bin Li (MDPI AG, 2019)
Food processing can affect the nutrition and safety of foods. A previous study showed that tannase and ultrasound treatment could significantly increase the antioxidant activities of green tea extracts according to in vitro evaluation methods. Since the results from in vitro and in vivo experiments may be inconsistent, the in vivo antioxidant activities of the extracts were studied using a mouse model of alcohol-induced acute liver injury in this study. Results showed that all the extracts decreased the levels of aspartate transaminase and alanine aminotransferase in serum, reduced the levels of malondialdehyde and triacylglycerol in the liver, and increased the levels of catalase and glutathione in the liver, which can alleviate hepatic oxidative injury. In addition, the differences between treated and original extracts were not significant in vivo. In some cases, the food processing can have a negative effect on in vivo antioxidant activities. That is, although tannase and ultrasound treatment can significantly increase the antioxidant activities of green tea extracts in vitro, it cannot improve the in vivo antioxidant activities, which indicates that some food processing might not always have positive effects on products for human benefits.